A Hybrid Watermarking Scheme For Medical Images (International Journal of Engineering and Computer Science, 2017)
This paper introduces hybrid watermarking scheme for medical images. We propose a watermarking scheme that can recover the original image from the watermarked one. Medical images require special safety and confidentiality because critical judgment is done on the information provided by medical images. Transmission of medical image via internet or mobile phones demands strong security and copyright protection in telemedicine applications. In the field of telemedicine confidentiality of a medical image can be achieved by hiding the Electronic Patient Record (EPR data)in corresponding medical images. Technique named Class Dependent Coding Scheme [2] and the modified difference expansion watermarking using LSB replacement in the difference of virtual border. The payload is formed by image hashing using MD5 [1]. The proposed techniques aim at increasing the data hiding capacity, so it can be used to protect vary images like military or medical images. The paper discusses the perspectives of digital watermarking in a range of medical data management and distribution issues, and proposes a complementary and/or alternative tool that simultaneously addresses medical data protection, archiving, and retrieval, as well as source and data authentication. The scheme imperceptibly embeds in medical images multiple watermarks conveying patient's personal and examination data, keywords for information retrieval, the physician's digital signature for authentication, and a reference message for data integrity control. Experimental results indicate the efficiency and transparency of the scheme, which conforms to the strict requirements that apply to regions of diagnostic significance.